3D Bioprinting of Heterogeneous Constructs Providing Tissue‐Specific Microenvironment Based on Host–Guest Modulated Dynamic Hydrogel Bioink for Osteochondral Regeneration. (15th March 2022) - Dai, Wenli; Zhang, Liwen; Yu, Yingjie; Yan, Wenqiang; Zhao, Fenyuan; Fan, Yifei; Cao, Chenxi; Cai, Qing; Hu, Xiaoqing; Ao, Yingfang
Abstract: 3D bioprinting is a promising strategy to develop heterogeneous constructs that mimic osteochondral tissue. However, conventional bioprinted hydrogels suffer from intrinsically weak mechanical strength, limited cell adaptability, and no sustained release of biochemical drugs, restraining their use as bioinks to emulate native osteochondral extracellular matrix. Herein, a novel host–guest modulated dynamic hydrogel is developed for 3D bioprinting heterogeneous cell‐laden constructs for osteochondral regeneration. Apart from gelatin methacryloyl (GelMA), this bioink consists of dopamine‐functionalized GelMA and acrylate β‐cyclodextrin and is crosslinked by host–guest interaction to develop the dynamic network for obtaining promoted cell adaptability, enhanced cell adhesion, reinforced mechanical strength, and tunable modulus. Moreover, based on the sustained drug release provided by the cavity of β‐cyclodextrin, a heterogeneous construct is constructed by employing kartogenin (a chondrogenic factor) into the upper zone with lower Young's modulus and melatonin (an osteogenic factor) into the bottom zone with higher modulus to mimic the osteochondral microenvironment. With the favorable regeneration results in vitro and in vivo, a broad application of this bioink in 3D bioprinting for tissues engineering is expected. Abstract : A novel bioink with enhanced cell adaptability, tunable modulus, and sustainable drug release is developed by combining supramolecular interactions, covalent bonds, and network tethering systems. Based on this bioink, a heterogeneous construct is successfully bioprinted with biomechanical and biochemical gradients to mimic the osteochondral microenvironment and simultaneously regenerate cartilage and subchondral bone, hence providing a versatile platform for tissue engineering.